Odpowiedzi

2010-02-14T19:06:25+01:00
A)x+2y=-2
2x-y=1

x=-2-2y
2x-y=1

x=-2-2y
2(-2-2y)-y=1

x=-2-2y
-4-4y-y=1

x=-2-2y
-5y=5/:(-5)

y=-1
x=-2-2*(-1)

y=-1
x=0

b) x+4y=-2
3x-8y=10

x=-2-4y
3x-8y=10

x=-2-4y
3(-2-4y)-8y=10

x=-2-4y
-6-12y-8y=10

x=-2-4y
-20y=16/:(-20)

y=-0,8
x=-2-4*(-0,8)

y=-0,8
x=-5,2

c)x-2y=3
-2x+y=0

x=3+2y
-2x+y=0

x=3+2y
-2(3+2y)+y=0

x=3+2y
-6-4y+y=0

x=3+2y
-3y=6/:(-3)

y=-2
x=3+2*(-2)

y=-2
x=-1


d) 2x+y=9
5x-4y=3

y=9-2x
5x-4y=3

y=9-2x
5x-4(9-2x)=3

y=9-2x
5x-36+8x=3

y=9-2x
13x=39/:13

x=3
y=9-2*3

x=3
y=3

Najlepsza Odpowiedź!
2010-02-14T19:10:06+01:00
A)
x+2y=-2
2x-y=1

x=-2-2y
2x-y=1

2(-2-2y)-y=1
-4-4y-y=1
-4y-y=1+4
-5y=5|:(-5)
y=-1
x=-2-2*(-1)
x=-2+2
x=0

b)
x+4y=-2
3x-8y=10

x=-2-4y
3(-2-4y)-8y=10
-6-12y-8y=10
-12y-8y=10+6
-20y=16|:(-20)
y=-16/20
y=-8/10
y=-4/5

x=-2-4 * (-4/5)
x=-2+ 3 1/5
x=1 ⅕

c)
x-2y=3
-2x+y=0

x=3+2y
-2(3+2y) +y=0
-6-4y +y=0
-3y=6|:(-3)
y=-2

x=3+2 * (-2)
x=3 -4
x=-1

d)
2x+y=9
5x-4y=3

y=9-2x
5x-4(9-2x)=3
5x-36+8x=3
5x+8x=3+36
13x=39|:13
x=3

y=9-2 * 3
y=9-6
y=3

e)
3x-2y=5
2x-y=4

-y=4-2x|(-1)
y=-4+2x

3x-2(-4+2x)=5
3x+8-4x=5
-x=5-8
-x=-3|:(-1)
x=3

y=-4 + 2 * 3
y=-4+6
y=2

f)
2x+9y=-9
-3x+3y=8

3y=8+3x|:3
y=8/3 + x
2x+9(8/3 +x)=-9
2x+24 +9x=-9
11x=-9-24
11x=-33|:11
x=-3

y=8/3 + (-3)
y=-1/3

g)
2x+3y=4
8x-5y=-1

2x=4-3y|:2
x=4/2-3/2y
x=2-3/2y
8(2-3/2y) - 5y=-1
16-12y-5y=-1
-17y=-1-16
-17y=-17|:(-17)
y=1
x=2-3/2 * 1
x=2-3/2
x=1/2